The Problems of IPAS Learning in the Merdeka Curriculum - Listriyanti Palangda; Desy Suyono; Niny Makaliwe (STKIP Singkawang, 2025)
This study aims to analyse teacher readiness and competency in implementing the Independent Curriculum in Natural and Social Sciences (IPAS) learning at SMA Negeri 2 Tondano. This study used a descriptive qualitative approach. Data collection was conducted through in-depth interviews with seven informants: the principal, the vice principal for curriculum, two IPAS teachers, and three 10th-grade students. Data analysis techniques used included data reduction, data presentation, and conclusion drawing to identify patterns, themes, and meanings emerging from the field data. The research focused on teachers' understanding of the Independent Curriculum concept, their ability to design project-based learning and assessment, and the use of technology in the learning process. The results indicated that the readiness and competency of IPAS teachers were still in the early adaptation stage. Teachers had attempted to implement the principles of the Independent Curriculum, but still face challenges in analysing Learning Outcomes (CP), formulating Learning Objectives (TP), developing Learning Objective Flows (ATP), and developing contextual teaching modules. Other obstacles included limited digital literacy, inadequate supporting facilities, and low ability to implement project-based learning. Institutional support from schools existed, but it was not optimal due to limited time, resources, and technical assistance from external parties. Therefore, continuous teacher competency strengthening through practice-based training, increased educational technology literacy, and collaboration between teachers are needed to realise integrative science and science learning in accordance with the spirit of Freedom to Learn.